(The effect of heating and soda concentration in the preparation of monoglyceride on Its Physical Characteristics) - Achmad Moestafa; Endah Djubaedah; Mariana - (Warta Industri Hasil Pertanian, 1995)
Glycerolmonolaurate is one of the emulsifiers used in food industries.The addition of such compound into food is to maintain its consistency, improve their texture homogenity and quality.It also stbilizes and thicens food mixture.Further it was understood,that the improvement of food characters depend on the method of emulsifier preparation.An experiment had been carried out to study the effect of heating time  and soda concertration on the Hydrophlyc Liphophylic Balance (HLB) value and its globular size when glycerolmonolaurate was prepared from coconut oil and glycerol.It was foundthat the duration of heating process and soda concertation significantly affected the globular size but did not against the HLB value.